On Some Properties of Weak Soft Axioms (European Journal of Pure and Applied Mathematics, 2017)
The aim of this paper is to initiate anddiscuss the properties and characterizations of soft semi-$T_{i}$and soft semi-$D_{i}$( for $i = 0, 1, 2$) spaces at soft point byanalyzing the relationship among them. We also introduce andexplore the properties of soft S-continuous functions.
Keywords: Soft sets; soft topology; soft semi-open (closed); soft semi-closure; soft semi-$D_{i}$(for $i = 0; 1; 2$)spaces; soft semi-$T_{i}$(for $i = 0; 2$ ) spaces; softS-continuous function.